(untitled) (Annals of Medical Research, 2021)
Aim: Physicians assessing newborns with risk factors for developmental dysplasia of the hip (DDH) have responsibility for early diagnosis. Written records of the fulfillment of such responsibility is required in medico-legal terms. The present study aims to examine the written records of the hospitals where patients with late-diagnosed DDH were born.Material and Methods: This retrospective study examined the records of the hospitals in which 53 DDH patients aged more than nine months were born. We investigated whether the requirements for the early diagnosis of these patients were recorded in written and interviewed with the obstetricians, pediatricians and family physicians who followed these patients. They were asked about their attitudes toward giving families informational documents about DDH and explaining protective measures verbally.Results: There was no written approved record that they have been informed about the disease in any institution and indicating that the responsibilities for the early diagnosis of these patients were fulfilled. The families were given informational documents in three of five private hospitals and in one university hospital. All of physicians informed the families about the early DDH diagnosis and the things to do, verbally. Conclusion: In case of late-diagnosed DDH, the society as well as the child and the child’s family get harmed socioeconomically. Therefore, it may pose a medico-legal problem. This risk increases more in countries where newborn screening policies are not adequately implemented. In conclusion, written documents taken from families about the early diagnosis of DDH will legally protect physicians and health care organizations.